2023
DOI: 10.1017/pds.2023.29
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Support the Improvement of Knowledge Transfers in Product and Production Engineering

Albert Albers,
Monika Klippert,
Moritz von Klitzing
et al.

Abstract: The product engineering process as part of the product life cycle includes product and production system development as well as production. In integrated product and production engineering (PPE), knowledge transfer is an important success factor. Optimizing the efficiency and effectiveness of knowledge transfers can, for example, support the avoidance of costly, production-related changes to the product design. The current state of research describes different models of knowledge transfer as well as factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Even though knowledge management is investigated by many researchers, they rarely focus on knowledge transfer as part of knowledge management particularly between product and production engineers. Since successful interdepartmental knowledge transfers face different challenges and obstacles, the InKTI method (Albers et al, 2023) was developed to support engineers in improving knowledge transfers in product and production engineering. Hence, it is necessary to ensure acceptance, applicability as well a contribution to the success of the method in practice (Blessing and Chakrabarti, 2009).…”
Section: Aim Of Research and Methodologymentioning
confidence: 99%
See 4 more Smart Citations
“…Even though knowledge management is investigated by many researchers, they rarely focus on knowledge transfer as part of knowledge management particularly between product and production engineers. Since successful interdepartmental knowledge transfers face different challenges and obstacles, the InKTI method (Albers et al, 2023) was developed to support engineers in improving knowledge transfers in product and production engineering. Hence, it is necessary to ensure acceptance, applicability as well a contribution to the success of the method in practice (Blessing and Chakrabarti, 2009).…”
Section: Aim Of Research and Methodologymentioning
confidence: 99%
“…To support the improvement of knowledge transfers in product and production engineering, the InKTI method has been developed (Albers et al, 2023), which is shown in Figure 1. This method is the basis for this research and has been validated in two field studies (Klippert, Schäfer et al, 2023;Klippert, Siebert et al, 2023) after the Live-Lab study presented in this paper.…”
Section: Improvement Of Knowledge Transfers In Product and Production...mentioning
confidence: 99%
See 3 more Smart Citations